CHONDROID LIPOMA AS SOFT TISSUE PSEUDOSARCOMA: LITERATURE REVIEW AND CASE REPORT - N. V. Vasilyev; S. V. Vtorushin; I. I. Anisenya; P. K. Sitnikov; S. A. Tabakaev; I. G. Frolova; A. V. Bogoutdinova; L. D. Zhuikova; P. V. Bairamov; S. I. Ponomareva; M. O. Tsvetukhin (Сибирский онкологический журнал)
Background. Pseudosarcomas of soft tissues can cause diagnostic and treatment challenges. On the one hand, it is difficult to make a nosological diagnosis based on a biopsy specimen of a tumor; on the other hand, it is difficult to determine the most appropriate treatment strategy based on a histological pattern.The purpose of the study was to analyze available literature data and systematize the histological characteristics of the chondroid lipoma and pseudosarcoma.Case description. We present the case of chondroid lipoma in a 57-year-old female patient with atypical clinical symptoms. This case shows the difficulties of differential diagnosis of soft tissue sarcomas. Using a clinical example of chondroid lipoma, a rare soft tissue tumor, and an analysis of literature data, the authors showed the importance of a detailed study of the obtained material, a qualified description of the morphological picture, in those cases when the diagnostic conclusion cannot be unambiguous about the malignancy of the tumor process. Additional biopsy is not always possible to clarify the histotype of the tumor. The presented observation shows the difficulties of differential diagnosis of soft tissue sarcomas. Minimally invasive biopsy provides no a full appreciation of histological structure; therefore, if there is a suspicion for chondroid lipoma, it is necessary to perform total surgical biopsy followed by a morphological study using the immunohistochemical method.